The Food Security Of The Household Recipient Of Food Independent Village Program In Central Sumba Regency - sabaora, yosua umbu osa; Heru Priyanto, Sony; Mary Prihtanti, Tinjung (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 2 (2021): Vol.15, No.2, 2021DO - 10.24843/SOCA.2021.v15.i02.p09, 2021)
The Food Independent Village Program was performed to give an impact on reducing the level of food and nutrition insecurity of the needy in rural areas. The success of program implementation can be seen from the level of food security of the household recipients. This research aimed to determine the level of food security based on 1) Share of Food Expenses (PPP), 2) Energy Sufficiency Rate (AKE), 3) Performance of household food security. The research method used was a survey method. Sampling used was a random sample (Random Sampling) with 85 respondents. The analysis method used was a cross-combination approach between the share of food expenses (PPP) and the level of household energy consumption (AKE). The results showed that based on AKE the distribution of food-secure households was 65.53% and food insecure was 36.47%. Meanwhile, based on PPP, the distribution of households that were food insecure was 40% and food secure was 60%. The performance of household food security in the food security category was 25.88 percent, food vulnerability was 40.00 percent, food shortage was 14.12 percent, and food insecurity was 20.00 percent. The proportion of households that were food insecure was still large, which means that efforts were needed to improve the food security of households who were the Food Independent Village program recipients.